2022
DOI: 10.3389/fendo.2022.841889
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fat Reducing Agents on Adipocyte Death and Adipose Tissue Inflammation

Abstract: Deoxycholic Acid (DCA), which is an FDA-approved compound for the reduction of submental fat, has evolved through an unanticipated and surprising sequence of events. Initially, it was used as a solvent for Phosphatidylcholine (PDC), which was thought to promote lipolysis, but it was later proven to be the bioactive component of the formula and is currently widely used as Kybella. It has also been used off-label to treat other types of fat deposits like lipomas, HIV lipodystrophy, and excess orbital fat. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…It is important to note that the existing literature suggests that injection lipolysis triggers a specific inflammatory response in adipose tissue, leading to cellular death, necrosis of fat tissue, and subsequent tissue fibrosis. [19][20][21] Further, the presence of fibrosis resulting from prior cheek injection lipolysis complicates the removal of the buccal fat pad, posing significant risks to the integrity of the buccal branch of the facial nerve and parotid duct. Buccal fat pad removal is particularly advantageous for individuals with round and chubby faces, as a substantial volume of fat should be excised to achieve an aesthetically pleasing result.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the existing literature suggests that injection lipolysis triggers a specific inflammatory response in adipose tissue, leading to cellular death, necrosis of fat tissue, and subsequent tissue fibrosis. [19][20][21] Further, the presence of fibrosis resulting from prior cheek injection lipolysis complicates the removal of the buccal fat pad, posing significant risks to the integrity of the buccal branch of the facial nerve and parotid duct. Buccal fat pad removal is particularly advantageous for individuals with round and chubby faces, as a substantial volume of fat should be excised to achieve an aesthetically pleasing result.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids (BAs) have been used as therapeutics for a variety of diseases, including primary biliary cirrhosis, cholesterol gallstone dissolution (Ursodiol; Chenodiol), , BA synthesis disorder (Cholbam), and local fat reduction (Kybella) . The FDA-approved NaDCA (Kybella) is used to treat double chin (submental fat depot), but the multiple injection regimen needed for this treatment causes bruising, pain, swelling, and vascular injury as side effects. In this report, we developed CDCA-loaded gelatin nanoparticles (CDCA-GNPs) with a controlled release profile and demonstrated that like NaDCA, CDCA-GNPs reduced subcutaneous adipocyte size.…”
Section: Cdca-gnps Promote Mitochondrial Respiration Of White Adipocy...mentioning
confidence: 99%
“…For instance, subcutaneous injection of sodium deoxycholic acid (NaDCA), Kybella, has been approved by the Food and Drug Administration (FDA) as a nonsurgical approach for reducing double chin. 8 However, the high doses and multiple injections of NaDCA needed to achieve these effects, which function primarily by promoting adipocyte cell death and subsequent inflammation within adipose tissue, restrict its application. 8 Unlike cytolysis, the utilization of lipids by promoting mitochondrial function is a well-documented alternative approach for reducing fat.…”
mentioning
confidence: 99%
See 2 more Smart Citations